2001
DOI: 10.1007/s100510170163
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetism and superconductivity in a model with extended pairing interactions

Abstract: The competition between antiferromagnetism and the d + id superconducting state is studied in a model with near and next near neighbour interactions in the absence of any on-site repulsion. A mean field study shows that it is possible to have simultaneous occurrence of an antiferromagnetic and a singlet d + id superconducting state in this model. In addition, such a coexistence generates a triplet d + id superconducting order parameter with centre of mass momentum Q = (π, π) dynamically having the same orbital… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In the present paper we study the coexistence of singlet dwave SC with SDWs and in particular we focus on the induced staggered triplet SC component and new behavior that may result because of the presence of these three order parameters. Several studies of the competition of unconventional SC with SDWs and the possibility of an emergent staggered π-triplet pairing are available [8][9][10][11][12][13]. For example, in [10,12] scattering by non-magnetic impurities is shown to stabilize a phase with all three order parameters (OPs) whereas in [11,13] the induced π-pairing is studied in the context of deviations from half-filling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present paper we study the coexistence of singlet dwave SC with SDWs and in particular we focus on the induced staggered triplet SC component and new behavior that may result because of the presence of these three order parameters. Several studies of the competition of unconventional SC with SDWs and the possibility of an emergent staggered π-triplet pairing are available [8][9][10][11][12][13]. For example, in [10,12] scattering by non-magnetic impurities is shown to stabilize a phase with all three order parameters (OPs) whereas in [11,13] the induced π-pairing is studied in the context of deviations from half-filling.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of the competition of unconventional SC with SDWs and the possibility of an emergent staggered π-triplet pairing are available [8][9][10][11][12][13]. For example, in [10,12] scattering by non-magnetic impurities is shown to stabilize a phase with all three order parameters (OPs) whereas in [11,13] the induced π-pairing is studied in the context of deviations from half-filling.…”
Section: Introductionmentioning
confidence: 99%
“…A study of the Hubbard model showed that for dwave superconductivity, coexistent SDW order and triplet superconductivity arise generally at half filling [29]. It was also shown that in a twodimensional spin lattice with com peting nearest and nextnearest neighbor interactions, dwave superconductivity can coexist with modulated triplet super conductivity [30]. Zhang derived a SO(5) symmetry principle that unifies antiferromagnetism and dwave superconductiv ity, and furthermore explains their coexistence [31].…”
Section: Theories For Exotic Magnetism In Superconductorsmentioning
confidence: 99%